Adherence to ACSM exercise guidelines and its influence on Fibromyalgia treatment outcomes: a meta-analysis of randomized controlled trials - Han, Tianran; Xi, Rui; Wang, Jialin; Yan, Huiqian; Li, Linhua (Frontiers in Physiology, 2024)
Background: The Fibromyalgia Syndrome (FMS) is a multifaceted chronic pain disorder that exerts a substantial impact on the overall state of health and quality of life of patients.Purpose: Investigate the effects of exercise therapy and adherence to the American College of Sports Medicine (ACSM) guidelines on treatment outcomes in FMS patients.The literature search, which concluded in October 2023, encompassed studies investigating the impact of exercise interventions on patients diagnosed with FMS and providing adequate data for calculating standardized mean differences (SMDs). The primary outcome measures encompassed the Fibromyalgia Impact Questionnaire (FIQ) and Health Assessment Questionnaire (HAQ), while secondary outcome measures comprised pain levels, sleep quality, fatigue, and mental health.Results: Among 4008 records, 19 studies (patients=857) were eligible for qualitative synthesis. The meta-analysis revealed that the SMD for overall state of health impact was -0.94 (95%CI -1.26, -0.63), and the pooled SMD for the subgroup with high adherence to ACSM guidelines was -1.17 (-1.65, -0.69). The SMD for the subgroup with low or uncertain adherence was -0.73 (95%CI -1.12, -0.34). The overall effects included a -1.21 (-1.62, -0.79) SMD for pain relief, with high adherence achieving a -1.32 (-2.00, -0.64) SMD and low adherence a -1.06 (-1.55, -0.57) SMD. Mental health improvements showed a -0.95 (-1.32, -0.57) overall SMD, with high and low adherence subgroups at -0.96 (-1.62, -0.30) and -0.94 (-1.28, -0.60), respectively. Sleep quality impact was -1.59 (-2.31, -0.87) overall, with high adherence at -1.71 (-2.58, -0.83) and low adherence at -1.11 (-1.88, -0.33). Fatigue impact had a -1.55 for high adherence and -1.35 (-2.03, -0.66) for low adherence. Conclusion: Exercise therapy can improve the overall state of health, pain, sleep, and fatigue of FMS patients, particularly when adhering to ACSM guidelines. However, adherence levels do not affect mental health gains, indicating a need for future research on psychological impact.